RATIONAL DRUG USE IN HEALTH SCIENCES STUDENTS AND AFFECTING FACTORS: A CROSS-CULTURAL OVERVIEW - Çelik, Hanife; Çevik Aktura, Seher; Kaplan, Mehmet (Inonu University, 2025)
This study aims to examine the Rational drug use (RDU) behaviours and influencing factors of Turkish and Syrian health sciences students to understand the cultural and social factors affecting medication practices. The data were collected between January-May (2024) by face-to-face survey method at a university in eastern Turkey. No sample selection was made among Syrian students and the whole population (n=182) was included in the study. In order to make a comparison, as many Turkish students as the number of Syrian students participating in the study were selected by simple random sampling method. The study was completed with 322 students (Syrian=161, Turkish=161). The mean RDU score of Syrian students was found to be statistically significantly higher than Turkish students (p<0.05). Age, gender, marital status, and grade had an effect size of 11% on Syrian students' RDU, while the same predictors had an effect size of 4% in Turkish students. When the cut-off point of the scale was taken as 35 points, it was determined that both Syrian and Turkish students had low RDU levels. In addition, sociodemographic factors were found to be effective in RDU. © 2025, Inonu University. All rights reserved.
Sağlık Bilimleri Öğrencilerinde Akılcı İlaç Kullanımı ve Etkileyen Faktörler: Kültürlerarası Bir Bakış
Keywords: Cultural diversity; Health; Rational drug; Student